COMMERCIAL CAMPAIGN STRATEGIES IN REDUCING IN THE USE OF SINGLE – USE PLASTIC PACKAGING THROUGH ZERO WASTE CAMPAIGN - Muflikha, Septia Nur; Arumsari, Rizki Yantami; Utama, Jiwa (eProceedings of Art & Design, 2024)
The issue of single-use plastic waste has become a global spotlight because of its negative impact on the environment. A number of large cities in Indonesia, including Jakarta, Semarang, Surabaya, Bandung, Palembang and Medan, have taken part in taking issue with this problem, with the city of Bandung ranking third in terms of the amount of potential waste reaching 1,301 tons every day. From data submitted by the Bandung City Environmental Service, it was revealed that more than 50 tons of plastic waste is produced every day, mainly from food and drink packaging. Studies conducted by the Bandung Institute of Technology show that around 70% of total city waste comes from plastic, posing risks to the environment and public health. Plastic food packaging not only has a negative impact on human health due to its chemical compounds, but is also detrimental to the environment due to its ability to decompose slowly. Lack of public awareness and understanding of the impact of single-use plastic on the environment and health is the main cause of this problem. In addition, small and large businesses that provide a lot of food and drink often choose single-use plastic or double-layer plastic because they are considered safe and able to maintain product quality. To overcome this, the proposed strategy is to launch a commercial campaign regarding zero waste management to change public perception, especially among students, workers and business owners, regarding the use of single-use plastic in food and beverage packaging. The campaign aims to promote environmentally friendly practices, encouraging the reduction, reuse and recycling of plastic waste. Keywords : commercial campaign, zero waste campaign, small and large business , single – use plastic packaging, Bandung